Chrześcijaństwo a reinkarnacja i metempsychoza w świetle polemiki Tertuliana z Platonem - Filipowicz, Adam M. (Vox Patrum, 2010)
The aim of this article is to show what the standpoint of Christianity in first centuries was among pagan conviction and teaching about reincarnation and metempsychosis. The author of this dissertation analyses Tertullian’s treatise On the Soul in context of Plato’ Dialogues. The first part of article puts in order meaning of terms: life after the death, immortality, resurrection, metempsychosis, metensomatosis, palingenesis, reincarnation, pre-existence of the soul. In the second part are discussed most important aspects of Plato’ view on the soul. Then are presented arguments (15) which Tertullian used to criticize Plato’ teaching about ideas and theory of anamnesis and to overthrow theory of reincarnation and metempsychosis. The conclusion takes recollection of standpoint and documents of the Church with reference to discussed matters.